Icelandic volcanic ash and the mid-Holocene Scots pine (Pinus sylvestris) pollen decline in northern Scotland - Blackford, J. J.; Edwards, K. J.; Dugmore, A. J.; Cook, G. T.; Buckland, P. C. (The Holocene, 1992)
A volcanic ash-layer in peat from northern Scotland has been identified and coincides exactly with an abrupt decline in Pinus sylvestris L. (Scots pine) pollen frequencies. This provides an isochrone (time-equivalent marker horizon) with which to investigate the timing of the Holocene 'pine-decline'. Furthermore, two possible causes of the southward shift of the range of Pinus in Scotland c. 4000 BP are suggested; a direct effect of acid pollution by chemicals produced by the eruption of Hekla (H-4), or a volcanically-induced climatic perturbation. These possibilities have wider implications for the influence of volcanism on postglacial environmental change.